Eksistensiale verstaan van die Ou Testament: Die teologiese arbeid van Antonius HJ Gunneweg - Boshoff, P. B. (Hervormde teologiese studies, 1987)
Existential understanding of the Old Testament: The theological work of Antonius HJ Gunneweg Gunneweg applies Bultmann's concept of existential understanding to the Old Testament. Existential interpretation means that the text must be laid out in terms of the possibilities of the human existence. The author shows how Gunneweg worked it out under the following headings: Israel; The beginning; Moses; One kingdom or two kingdoms; Paul; Sola scriptura instead of salvation history; Word. The result is that Gunneweg comes to a unique understanding of the relationship between the Old and New Testaments.